Оцінка контрейлерних перевезень та підвищення їх ефективності - Кравченко, Катерина; Вовк, Ірина; Литвиненко, Максим (Видавництво Львівської політехніки, 2013)
The article presents statistics of freight transportation for the years 2002-2013. Held the analysis of the shortcomings of road and rail transport modes. Performed classification methods unloading automotive vehicles, which are transported on railway platforms. Proposed objective function for evaluating the effectiveness of a piggyback, the physical meaning of which is to try to minimize material costs, harmful emissions, time, drag, dirt carried by road rolling, volumes of stolen goods. Improved design of the railway platform, thus improving safety, reduce pollution carried by car rolling stock and reduce the aerodynamic drag of rolling stock.
Keywords: статистика; вантажні перевезення; контрейлерні перевезення; цільова функція; розбірний каркас; ребра жорсткості; тент